THE EFFECTIVENESS OF ARTICULATE STORYLINE ON PROBLEM-SOLVING ABILITY AND STUDENT SELF-CONFIDENCE - Muslimah, Amelia; Nasrullah, Anton; Putri, Alyfha; Dzakiroh, Finda; Fatimah, Fatimah; Ratnasari, Silvia (Edupedia Publisher, 2023)
In education, many students need more confidence in problem-solving and a lack of confidence. This study compares the problem-solving abilities and mathematical confidence of students who use Articulate Storyline media versus traditional learning. The design of this study was quasi-experimental with the nonequivalent control group. The experimental class uses Articulate Storyline media, while the control class uses traditional learning. Students from X TKI 6 (Experiment) and X TKI 5 (Control) participated in this study. Mathematical problem-solving ability tests and self-confidence questionnaires were used to collect data for this study. Data analysis using the Mann-Whitney test revealed that Articulate Storyline media substantially increased students' problem-solving skills and mathematical confidence.